Triple-positive non-small cell lung cancer harboring EGFR mutation, ALK rearrangement, and high PD-L1 expression: a case report and literature review - Mao, Mengjie; Tao, Qingxiu; Zuo, Zhuo; Ge, Jun; Tian, Yuke; Liu, Bin (Frontiers in Oncology, 2026)
BackgroundEpidermal growth factor receptor (EGFR) mutations and anaplastic lymphoma kinase (ALK) rearrangements are typically considered mutually exclusive in non-small cell lung cancer (NSCLC). However, rare cases with coexisting EGFR/ALK alterations and high programmed death ligand-1 (PD-L1) expression, termed “triple-positive” NSCLC, have been reported. Optimal treatment strategies for this unique subgroup remain undefined.Case presentationWe describe a 54-year-old woman with stage IV lung adenocarcinoma harboring an EGFR exon 19 deletion, ALK–EML4/KIF5B fusion (V3a/b), and high PD-L1 expression (TPS = 90%). The patient received first-line osimertinib combined with pemetrexed/cisplatin, achieving durable disease control for 17 months. Upon progression, rebiopsy and next-generation sequencing (NGS) revealed persistent ALK fusion and newly acquired ERBB2 amplification. Treatment was switched to alectinib, leading to significant tumor regression and partial response.ConclusionThis case illustrates that in triple-positive NSCLC, initial EGFR-TKI combined with chemotherapy can achieve long-term control, while dynamic molecular profiling at progression is essential for identifying resistance mechanisms. Sequential targeted therapy guided by NGS remains a cornerstone for precision management in this complex molecular subtype.